(untitled) (ResearchJet Journal of Analysis and Inventions, 2022)
This article deals with the problems of aesthetic education of students in the lessons of the Russian language and literature. The characteristic features of techniques and methods that allow you to see the beautiful in art and in life are analyzed. Particular attention is drawn to the teacher’s word as the first step towards the student’s thought in his aesthetic education. Identified and substantiated the need for joint work of students in the classroom to overcome difficulties, a small victory over oneself. As a result of such work, the child learns to feel the beauty and admire it.